2010
DOI: 10.1016/j.bcp.2010.06.052
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanisms of phenothiazine-induced mitochondrial permeability transition: Thiol oxidation, strict Ca2+ dependence, and cyt c release

Abstract: Phenothiazines (PTZ) are drugs widely used in the treatment of schizophrenia. Trifluoperazine, a piperazinic PTZ derivative, has been described as inhibitor of the mitochondrial permeability transition (MPT). We reported previously the antioxidant activity of thioridazine at relatively low concentrations associated to the inhibition of the MPT (Brit. J. Pharmacol., 2002;136:136-142). In this study, it was investigated the induction of MPT by PTZ derivatives at concentrations higher than 10 microM focusing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…In contrast, it has been recently shown that a higher concentration of trifluoperazine can induce MPT in isolated mitochondria and apoptosis of melanoma cells (Gil-Ad et al 2006;Cruz et al 2010). In the report by Cruz et al (2010), it has been shown that phenothiazine derivatives such as trifluoperazine and thioridazine induced swelling of isolated mitochondria and cytochrome c release. Concordantly, we observed neurotoxicity at a similar concentration range and we could detect cytochrome c release following perphenazine or trifluoperazine treatment in the cultured cells.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, it has been recently shown that a higher concentration of trifluoperazine can induce MPT in isolated mitochondria and apoptosis of melanoma cells (Gil-Ad et al 2006;Cruz et al 2010). In the report by Cruz et al (2010), it has been shown that phenothiazine derivatives such as trifluoperazine and thioridazine induced swelling of isolated mitochondria and cytochrome c release. Concordantly, we observed neurotoxicity at a similar concentration range and we could detect cytochrome c release following perphenazine or trifluoperazine treatment in the cultured cells.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, trifluoperazine at this concentration range has been shown to partially protect cells from oxidative damage (Liu et al 2011). In contrast, it has been recently shown that a higher concentration of trifluoperazine can induce MPT in isolated mitochondria and apoptosis of melanoma cells (Gil-Ad et al 2006;Cruz et al 2010). In the report by Cruz et al (2010), it has been shown that phenothiazine derivatives such as trifluoperazine and thioridazine induced swelling of isolated mitochondria and cytochrome c release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenothiazines are commonly used in combination with other drugs in antipsychotic treatment, showing also various biological activities involving antibacterial, antiplasmid, antitumor and antihelmintic properties [49, 50]. These compounds have been shown to possess cytostatic and cytotoxic effects in a variety of non-CNS cells [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Some drugs which are routinely used in the treatment for schizophrenia, psychosis and anxiety, such as phenothiazines (PTZ), are known to act through stimulation of mitochondrial permeability, thus enhancing OS in target cells, although at the expenses of increased hepatotoxicity [154]. Conversely, trifluoperazine, a piperazinic PTZ derivative, has been reported to show antioxidant activity at relatively low concentrations, which has been associated with its inhibition of mitochondrial permeability [155].…”
Section: Mood and Psychiatric Disorders And Os-targeting Approachesmentioning
confidence: 99%